The problem of freedom in native philosophy and religiology - Zoya Shwed (Cхід, 2013)
The article studies the characteristics of the native philosophical understanding of freedom. Established: The specifics of interpretations of this phenomen is closely related to those historical circumstances which accompanied the process of "ethno-religio-genesis" in Ukrainian.